The Influence of Service Quality on Revisit Intention through Customer Satisfaction as a Mediating Variable: A Study at Adiksi Coffee in Bandar Lampung - Dinnisa Tiara Annastasya; Dwi Asri Siti Ambarwati; Angga Febrian (International Forum of Researchers and Lecturers, 2025)
This research seeks to examine the effect of service quality on revisit intention, with customer satisfaction acting as a mediating variable, at Adiksi Coffee in Bandar Lampung. The study employed a survey method using questionnaires, gathering responses from 160 individuals who had previously visited Adiksi Coffee. The data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) to assess the relationships among service quality, customer satisfaction, and revisit intention. The analysis utilized the SERVQUAL dimensions for measuring service quality, alongside performance, expenses and overall expectation dimensions for customer satisfaction, and the Theory of Planned Behavior (TPB) dimensions for revisit intention. The findings revealed that service quality significantly and positively influences customer satisfaction; service quality also directly and positively impacts revisit intention. Additionally, customer satisfaction was found to have a significant positive effect on revisit intention and served as a mediator in the relationship between service quality and revisit intention. This study highlights the critical role of service quality in shaping customer satisfaction and revisit intention within the coffee shop sector, particularly at Adiksi Coffee. These insights offer valuable practical implications for coffee shop operators aiming to enhance customer satisfaction and encourage repeat visits by focusing on service quality improvements.